Audiometric evaluation in individuals with mucopolysaccharidosis - Marcela Rosana Maia da Silveira; Ana Karina Lima Buriti; Ana Maria Martins; Daniela Gil; Marisa Frasson de Azevedo (Clinics, 2018)
OBJECTIVES: To characterize the audiometric evaluation and acoustic immittance measures in different types of mucopolysaccharidosis. METHOD: Fifty-three mucopolysaccharidosis patients were evaluated. The classification consisted of type I (Hurler syndrome, Hurler-Scheie and Scheie syndrome), type II (Hunter syndrome), type III (Sanfilippo syndrome), type IV (Morquio syndrome), and type VI (Maroteaux-Lamy syndrome). Immittance audiometry and play or conventional threshold tone audiometry were used to obtain auditory thresholds and were chosen according to the patient’s chronological age and ability to understand/respond to the procedure. The findings were analyzed using descriptive statistics and considering the recommendations for research involving human beings contained in Resolution CNE N° 466/2012. RESULTS: Fifty-one subjects (96.2%) had hearing loss, and the conductive type was the most frequent. Only two (3.8%) patients presented bilateral thresholds within normal limits, one with type IV mucopolysaccharidosis and the other with type VI. There were 11 individuals (20.8%) with mucopolysaccharidosis type I with mixed hearing loss, 9 (16.9%) individuals with type I with conductive hearing loss and 9 (16.9%) with type VI with conductive hearing loss. Mild hearing loss was most common (37.3%), followed by moderately severe hearing loss (36.3%). The type B tympanometric curve (80.4%) was the most frequent. CONCLUSIONS: Most of the individuals with mucopolysaccharidosis types I, II, III, IV and VI presented mixed or conductive hearing losses of mild to moderately severe degree, type B tympanograms and an absence of contralateral acoustic reflexes.